Electroacupuncture for the treatment of cancer pain: a systematic review and meta-analysis of randomized clinical trials - Zhang, Junning; Wu, Weizhen; Ren, Yuehan; Yuan, Yi; Jia, Liqun (Frontiers in Pain Research, 2023)
Abstract Objective: This paper aims to review the current evidence on electroacupuncture as an effective and safe therapy for cancer pain management. Methods: Five databases were searched from their inception through November 11, 2022. Only the randomized controlled trials that meet the eligibility criteria will be finally included in the study. Literature screening and data extraction were performed independently by two researchers, and Cochrane’s software RevMan 5.3 will be used for meta-analysis. Results: A total of 17 RCTs met our inclusion criteria. We used 8 indicators to estimate the meta-analysis results, most of which proved statistically significant, including VAS scores, NRS scores, and KPS scores. To be specific, VAS scores (MD = -1.41, 95% CI: -2.42 to -0.41, P = 0.006) and NRS scores (MD = -1.19, 95% CI: -1.72 to -0.66, P < 0.0001) were significantly lower in the treatment group compared to the control group. The treatment group's KPS scores (MD=5.48, 95% CI: 3.27 to 7.69, P < 0.00001) were higher than those of the control group. Also, in the treatment group, the number of burst pain (MD = -2.66, 95% CI: -3.32 to -1.99, P < 0.00001) and side effect rates (RR = 0.51, 95% CI: 0.39 to 0.67, P < 0.00001) greatly reduced, while the response rate (RR = 1.17, 95% CI: 1.09 to 1.26, P < 0.0001) significantly increased compared to the control group. Conclusion: This study demonstrates the advantages of electroacupuncture in the treatment of cancer pain. Meanwhile, rigorous RCTs should be designed and conducted in the future to further demonstrate the exact efficacy of electroacupuncture.